Enhancing Middle School Students' Scientific Literacy Through Inquiry-Based Learning In Environmental Education - Abdullah, Muhammad Ikram; Kusuma, Javier; Abrar, Rangga Nasution (Lembaga Publikasi Ilmiah Nusantara, 2025)
Scientific literacy is essential for preparing students to face environmental challenges and make informed decisions in a complex, technology-driven society. This study aims to investigate the effectiveness of inquiry-based learning (IBL) in enhancing middle school students’ scientific literacy within the context of environmental education. A quasi-experimental design was employed involving 120 students from two public middle schools in Pinang, Malaysia. The experimental group received instruction using inquiry-based learning strategies, while the control group was taught using conventional methods. Data were collected through a pre-test and post-test scientific literacy assessment and analyzed using paired and independent samples t-tests. The results revealed that students in the experimental group showed significantly higher improvement in scientific literacy, particularly in understanding scientific concepts, applying knowledge to real-world issues, and evaluating environmental solutions critically. The inquiry-based learning model fostered active participation, critical thinking, and problem-solving skills by engaging students in observing, questioning, experimenting, and drawing conclusions based on evidence. Moreover, student interviews and classroom observations indicated increased motivation and environmental awareness among participants. These findings underscore the value of integrating inquiry-based approaches in environmental education to cultivate scientifically literate individuals who are capable of making responsible environmental decisions. The study recommends broader implementation of inquiry-based learning across science curricula to support long-term environmental literacy development in students.